2015
DOI: 10.3928/01484834-20141224-04
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Embedded Audio Feedback on Writing Assignments

Abstract: The purpose of this pilot study was to compare embedded audio feedback (EAF), which faculty provided using the iPad(®) application iAnnotate(®) PDF to insert audio comments and written feedback (WF), inserted electronically on student papers in a series of writing assignments. Goals included determining whether EAF provides more useful guidance to students than WF and whether EAF promotes connectedness among students and faculty. An additional goal was to ascertain the efficiency and acceptance of EAF as a gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Also, students were encouraged to support; learn and mentor each other on the discussion forums in light of peer learning can improve the overall quality of student learning [8]. VC were designed to strengthen interaction amongst students, and 'teacher-presence' plays a crucial role in building a sense of belonging to the learning community and in improving student retention [9]. However, it is observed that maintaining a strong sense of 'teacher-presence' in online education (e.g.…”
Section: Methods Of Observation and Toolmentioning
confidence: 99%
“…Also, students were encouraged to support; learn and mentor each other on the discussion forums in light of peer learning can improve the overall quality of student learning [8]. VC were designed to strengthen interaction amongst students, and 'teacher-presence' plays a crucial role in building a sense of belonging to the learning community and in improving student retention [9]. However, it is observed that maintaining a strong sense of 'teacher-presence' in online education (e.g.…”
Section: Methods Of Observation and Toolmentioning
confidence: 99%